Social life and political trust in China: Searching for machers and schmoozers - Huang, Yinxuan (International Political Science Review)
Previous literature has provided little evidence regarding the ways in which China$1 (Bs burgeoning social life and rapid urbanization shape Chinese people$1 (Bs level of trust in their government leaders. This article builds on Robert Putnam$1 (Bs conceptualization of maching and schmoozing as formal and informal forms of social involvement, respectively. Using the 2012 Chinese General Social Survey, we identify four types of participants in social involvement, namely the inactives, machers, schmoozers and all-rounders, to untangle various aspects of social life in China. Our empirical analysis shows that the sociodemographic positions of the four types of social involvement are largely distinct. Our findings also contribute to the study of political trust by offering insight into the complicated associations between social involvement, hukou status and political trust in contemporary Chinese society. - Reproduced.s